TRANSHUMANCE OU STRUGGLEFORLIFISME CULTUREL AFRICAIN ? CAS DE LA CULTURE SONGYE - Kasendue, Constantin (IJRDO - Journal of Social Science and Humanities Research, 2022)
The crumbling of African traditional cultural identity towards the global cultural revolution touching on basic of African had stimulated the designation need against tragic mimicry of certain cultures and mindsets imported during colonization and post – modernity. This reality had harmful consequences on post-colonial African societies.As example, I can cite: triteness of life, sacred sense, and the ridden of individualist mentalities, disacralization of African traditional rites, consequently, the disappearance of African identity dislocated thereby the stem of African civilization revival in its essential compartments.It is in such perspective that it is worth asking oneself:How surmount the acculturation conceived and instrumented by global Cultural Revolution? African cultural traditions survive don’t they depend upon the adaptation of the new order without losing one’s soul or rejecting one’s own traditions?